1998
DOI: 10.1007/s004649900776
|View full text |Cite
|
Sign up to set email alerts
|

Port site metastases and recurrence after laparoscopic colectomy

Abstract: The laparoscopic approach has a recurrence rate similar to that for open procedures for colon cancer. However, additional follow-up of these patients is needed before we can determine whether or not the laparoscopic approach influences overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
14

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(131 citation statements)
references
References 17 publications
4
113
0
14
Order By: Relevance
“…Although prospective, this study allowed patients to chose which type of surgery was performed, raising questions regarding selection bias. Lacy et al, 29 in a prospective and randomized trial, reported a recurrence rate of 16.1% among 31 laparoscopic-assisted resections after a mean follow-up of 21 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although prospective, this study allowed patients to chose which type of surgery was performed, raising questions regarding selection bias. Lacy et al, 29 in a prospective and randomized trial, reported a recurrence rate of 16.1% among 31 laparoscopic-assisted resections after a mean follow-up of 21 months.…”
Section: Resultsmentioning
confidence: 99%
“…Of comparable series, Lumley et al 27 reported a recurrence rate of 6.3% to a median follow-up of 33 months, which is superior to most data from open series. A small randomized trial from Lacy et al's 29 group in Barcelona reported recurrence in 16.1% of 31 laparoscopic procedures compared with 15% of open colectomies during a mean follow-up of 21 months. Given that this study did not include rectal cancer cases, and that the follow-up period is shorter, the recurrence figures reported are comparable to those of the present series.…”
Section: Discussionmentioning
confidence: 99%
“…The first RCT looking at late outcomes of laparoscopic surgery for colonic cancer was reported by Lacey Trials. 7 Significant advantages were seen with regards to reduced blood loss, early return of intestinal motility, lower overall morbidity and shorter duration of hospital stay in the laparoscopic-assisted group. Also, univariate analysis established a significantly better cancer-related survival in the laparoscopic group, but subgroup analysis stratified for tumour stage revealed that survival benefit was mainly limited to stage III disease.…”
Section: Discussionmentioning
confidence: 91%
“…There are a number of concerns such as the ability of the laparoscopic approach to allow a precise total mesorectal excision, as championed by Heald and Ryall [11]. Such concerns are appropriate; however, studies to date have consistently failed to demonstrate any detriment in terms of disease recurrence and survival consequent to a laparoscopic approach to colorectal cancer [12,13,14,15,16,17]. …”
Section: Indications and Contra-indicationsmentioning
confidence: 99%